Innovation systems and regional clustering: the diffusion of knowledge for sustainability issues - Rita Santos; Walter Leal; Evando Mirra (European Regional Science Association (ERSA), 2010)
The innovation systems perspective is primarily concerned with the knowledge flow and diffusion and its positive impact of stimulating economic growth. In innovation systems observed at the regional level there is a tendency of technologically dynamic production to become spatially concentrated in clusters, where individuals and organizations possessing specialized knowledge and technological capabilities. Consequently, results appear as collective efficiency, competitive advantage and economic benefits. During the 1980s and early 1990s, Brazil set up an important telecommunications cluster in Campinas region, fostered by government policies, and evolved around a telecom R&D Centre. Several small high-tech firms were established, grew, competed and cooperated with the local infrastructure and multinational corporation (MNC) subsidiaries. These, in turn, increased their local technological efforts and engaged in joint technological programs with local partners. In this paper the relation between innovation and knowledge is illustrated by the high-technology cluster of Campinas. It also discusses clustering enabling technology for environmental sustainability issues and regional implications.
Keywords: 330; development; knowledge spillovers; region; innovation systems; sustainability